Setting health research priorities using the CHNRI method: II. Involving researchers - Sachiyo Yoshida; Simon Cousens; Kerri Wazny; Kit Yee Chan (Edinburgh University Global Health Society, 2016)
Large groups of researchers who agree to offer their research ideas and then score them against pre-defined criteria are at the heart of each CHNRI priority-setting exercise. Although the roles of funders and other stakeholders are also very important, much of the exercise is focused on selecting and engaging a large group of researchers, obtaining their input and analysing it to derive the initial results of the process. In a sense, a CHNRI exercise serves to "visualise" the collective knowledge and opinions of many leading researchers on the status of their own research field. Through a simple "crowdsourcing" process conducted within the relevant research community, the CHNRI approach is able to collate a wide spectrum of research ideas and options, and come to a judgement on their strengths and weaknesses, based on the collective knowledge and opinions of many members of the research community. In doing so, it provides valuable information to funders, stakeholders and researchers themselves, which is obtained at low cost and with little time necessary to conduct the exercise.